The effectiveness of STEM and religion-based worksheets to improve problem solving skills and nutritional awareness - zuhair abdullah; Tresia Istiqomah; Ratna Sari; Ratna Sari (JURNAL BIOEDUKATIKA, 2022)
This study aims to: 1) determine the effectiveness of student worksheet based on Science, Technology, Engineering, Mathematics, and Religion (STEM-R) to improve problem solving skills; 2) determine the effectiveness of STEM-R-based student worksheets to increase students’ nutritional awareness. This is a quasi-experimental research with a pretest posttest control group design. Analysis of the increase in pretest and posttest data for control and experimental classes was carried out using normalized gain data. Quantitative data analysis was performed using the t-test to test the significance of the difference in gain between the control and experimental classes. The results of this study are: 1) the use of STEM-R-based LKPD is effective to improve problem solving skills, the effectiveness is proven by the acquisition of a percentage gain of 66% with a fairly effective category. 2) the use of STEM-R-based LKPD is effective to increase nutritional awareness, the effectiveness is proven by the acquisition of a percentage gain of 58% with a fairly effective category. The quantitative effectiveness of the problem-solving skill gain data and nutritional awareness between the control and experimental classes was also proven by the results of the t-test with a p value (sig) of 0.000 less than 0.05 (Sig <0.05)